LAUGHTER TAXONOMY DISCOURSE IN THE RENAISSANCE LITERARY CONSCIOUSNESS - Oleg V. Rodnyi (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
The article is devoted to the analysis of the comic Renaissance literature through the prism of individual works in order to identify the main comic functions. The Renaissance laughter culture formation is one of the urgent and underdeveloped problems of modern humanities adressed to the study of the Renaissance. The purpose of our work and the tasks dictated by it – in the context of the «laughter word» of the Renaissance to reveal the main comic functions in the literature of this period that were formed by a new worldview and new relationships amoung people. The stated goal determines the need to use hermenegutic (analysis of literary texts), typological (comparison of various comic functions), historical (solution of a literary problem in the context of a historical epoch) research methods. The “discovery of the world and man” that was characteristic of the Renaissance also took place in fiction. Renaissance realism turned it’s face to the everyday life of a person, and literature willingly accepted a new theme for itself including comedy. The article highlights various social functions of laughter that were used in Renaissance literature. Recreational laughter function is the original and oldest one. Laughter is evidence of pleasure, relaxation, rest. This laughter’s function is necessary for the normal functioning of not only an individual, but society as a whole. Such works as fables, schwankis, facies, “Gargantua and Pantagruel” by Rabelais, “Don Quixote” by Cervantes, comedies by W. Shakespeare, their main task was entertaining first of all. Their laughter is a clear evidence of inner freedom and healthy vitality. Laughter is a social phenomenon, and therefore it must meet the well-known requirements of people livihg together. Therefore, one of the main of functions is social. Laughter should be a kind of social gesture; it frees society from mechanical rigidity. We single out this function in Luigi Pulci’s poem “Morgante”. Funny and serious, faith and disbelief, naivety and scientific coexist side by side in this work, defining its heroic-comic character. The ontological aspects of laugher are closely related to cognitive ones. The cognitive laughter function has a great importance in revealing social negative aspects, in bringing them to the point of absurdity and thereby revealing their inconsistency and the obligation to eliminate them. This laughter function is represented in Sebastian Brant`s poem “The Ship of Fools”, in Rotterdams satire “The Praise of Folly”, in F. Rabelais` novel “Gargantua and Pantagruel”. Laugh as an effective social sanction (the sanctioning function of laughter) is presented in Cervantes` novel. The main thing in Don Quixote is not so much a parody of chivalry as a realistic disclosure of new social conditions and worldview discoveries, which was a parody of a past life. At the end of the novel, realizing his madness, Don Quixote thereby frees himself from his comic. The novel takes on a pronounced tragic connotation. The title character recognizes his doom and ceases to be pathetic, he becomes a knight of the “sad image”, he dies not a pathetic madman, but a humble Christian. The various functions of laughter, presented in the Renaissance literature were an effective tool in the fight against the remnants of the Middle Ages and the establishment of a new worldview.